A Swing Arm Trainer Prototype: Improving Basic Discus throwing Technique Skills in Junior High School Students - Tegar Bhakti Sandiyudha; Sapta Kunta Purnama; Slamet Riyadi (LPPM Undiksha, 2025)
The limited availability of training aids that are safe, ergonomic, and aligned with biomechanical principles has reduced the effectiveness of discus throw technique instruction. This study aims to develop, evaluate the feasibility of, and analyze the effectiveness of a Swing Arm Trainer prototype in improving discus throw technique and throwing strength among novice athletes. The study employed a Research and Development (R&D) approach using the ADDIE development model. The research subjects consisted of 20 students who also served as trial participants, including 5 students in a small-scale trial and 15 students in a large-scale trial, selected using a total sampling technique. Data collection methods included observation, literature review, and questionnaires, with research instruments comprising a discus throw performance test and evaluation questionnaires completed by subject-matter experts and media experts. Data analysis was conducted using a paired-sample t-test with a 5% significance level, assisted by SPSS software. The results indicate that the Swing Arm Trainer prototype is valid and reliable, feasible for use based on expert evaluations, and effective in improving discus throw technique and throwing strength. The findings demonstrate that the use of the Swing Arm Trainer prototype leads to a significant improvement in discus throw skills among novice athletes. This study implies that the Swing Arm Trainer can serve as an alternative training medium that is safe, effective, and practical for discus throw instruction and training in schools and sports clubs.